Partial pericardial agenesis in a dog - Bezerra, Lorena S.; Eloi, Rômulo Santos A.; Santos, André L.R.M.; Oliveira, Letícia B. de; Araujo, José Vanderlei; Blume, Guilherme R. (Brazilian Journal of Veterinary Pathology, 2022)
Pericardial defects are considered rare in animals and humans. Pericardial agenesis is characterized by partial or total pericardial sac malformation. Here is reported a case of apical partial pericardial agenesis in an adult mixed-breed male dog referred for necropsy. The pericardial sac was absent from the apical region up to the middle area of the ventricles resulting in a bilateral ventricular compression by the remaining pericardium changed the organ conformation. Microscopically, there was evidence of neutrophilic and hemorrhagic myocarditis with cardiomyocyte atrophy and interstitial fibrosis. Agenesis is often a subclinical disorder, and it is an incidental postmortem finding in most cases; however, it can cause complications in cases of cardiac structure herniation.